2010
DOI: 10.1038/ijo.2010.168
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery in a patient with complete MC4R deficiency

Abstract: Bariatric surgery is often successful for treatment of severe obesity. The mechanisms of weight loss after bariatric surgery and the role of central energy homeostatic pathways in this weight loss process are not well understood. The study of individuals with complete loss of function of genes important in the leptin-melanocortin system may help establish the significance of these pathways for weight loss after bariatric surgery. We describe the outcome of bariatric surgery in an adolescent with compound heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 24 publications
2
47
0
1
Order By: Relevance
“…Laparoscopic adjustable gastric banding did not result in a long-term weight reduction in an 18-years old patient with complete MC4R deficiency [217], and was associated with a high risk of conversion to bypass operations in individuals with partial MC4R deficiency [218]. On the other hand, three studies confirmed that Roux-en-Y gastric bypass surgery was an efficient strategy to lose weight in MC4R mutation carriers [219][220][221].…”
Section: Obesity-predisposing Gene Variants Interact With Bariatric Smentioning
confidence: 93%
“…Laparoscopic adjustable gastric banding did not result in a long-term weight reduction in an 18-years old patient with complete MC4R deficiency [217], and was associated with a high risk of conversion to bypass operations in individuals with partial MC4R deficiency [218]. On the other hand, three studies confirmed that Roux-en-Y gastric bypass surgery was an efficient strategy to lose weight in MC4R mutation carriers [219][220][221].…”
Section: Obesity-predisposing Gene Variants Interact With Bariatric Smentioning
confidence: 93%
“…Thus, MC4R might well be important in the efficacy of bariatric surgical procedures. MC4R-deficient rats have been developed recently (18), and their relatively larger size makes the rat better suited than the mouse for mechanistic studies of bariatric surgery.Although the impact of MC4R mutations has been studied in combination with RYGB and gastric banding [a procedure that physically limits the diameter of the upper part of the stomach to reduce food intake (3,4,14)], it is unknown whether VSG still has beneficial effects in humans or rodents that are partially or completely deficient for MC4R. Therefore, we used wild-type (WT), Mc4r ϩ/Ϫ , and Mc4r Ϫ/Ϫ rats (18) to determine whether MC4R function is necessary for producing the beneficial effects of VSG with regard to body weight, glucose metabolism, and macronutrient preference.…”
mentioning
confidence: 99%
“…For example, older people and people with type 2 diabetes tend to lose less weight. Interestingly, the effects of bariatric surgery on weight loss appear to be dependent on MC4R in homozygous knockout animal models (71) and in humans with complete MC4R deficiency (72). However, patient heterozygosity for obesity-producing MC4R mutations does not affect the response to bariatric surgery (73,74).…”
Section: Physiological Mechanisms and Effectiveness Of Bariatric Surgerymentioning
confidence: 99%